Body balance in judokas - Maslinski, J.; Witkowski, K.; Cieslinski, W. (Journal of Combat Sports and Martial Arts, 2016)
Introduction. One of the objectives of a judo contest is to gain advantage by throwing the opponent onto the mat. In order to create the best possible mechanical conditions for a throw, a judoka tries to unbalance the opponent. The opponent is thrown off balance and will find it more difficult to defend himself or herself against the throw. However, an unbalanced opponent is by no means a passive opponent. His or her task is to try to stay on balance. Maintaining balance also depends on e.g. a judoka`s morphological features, including body mass and body height, height at which the judoka is gripped during throwing, and position of the centre of gravity. The height of the grip influences the arm of the rotational force used in off-balancing and the arm - the torque. Bearing the above in mind, the authors of the present study decided to examine body balance in judokas. The objective was to compare body balance in judokas at various levels (lower junior, junior and senior category) in terms of both their age and training experience. The experimenters compared their static and dynamic balance. The following research hypotheses were adopted: 1. Calendar age has a considerable impact on the development of balance in judokas. 2. Judo training is of crucial importance to the development of dynamic and static balance in judokas. 3. Body balance improves with age and with training experience. Material and methods. The study featured 84 active judokas aged between 15 and 42, who were members of Wroclaw judo clubs. Two tests were used to check their balance. Dynamic balance was measured by means of the Walking Test (walking over a special truss) developed by Ewaryst Jaskólski [2]. Static balance was measured by means of the Flamingo Test [3]. Results. The results show that dynamic balance improves with calendar age and training experience. This may be linked to the nature of the discipline, which involves being constantly in motion, changing the position of the body and loosing balance during contests. Dynamic balance is statistically significantly different between the lower junior and junior categories. On the other hand, static balance does not improve with calendar age. The researchers have even noted a regression in the junior category, which may be linked to a rapid growth in body height, changes in body proportions etc.